A comprehensive review of adverse events to drugs used in COVID‐19 patients: Recent clinical evidence. (27th February 2022) - Ferreira‐da‐Silva, Renato; Ribeiro‐Vaz, Inês; Morato, Manuela; Junqueira Polónia, Jorge
Abstract: Background: Since the breakthrough of the pandemic, several drugs have been used to treat COVID‐19 patients. This review aims to gather information on adverse events (AE) related to most drugs used in this context. Methods: We performed a literature search to find articles that contained information about AE in COVID‐19 patients. We analysed and reviewed the most relevant studies in the Medline (via PubMed), Scopus and Web of Science. The most frequent AE identified were grouped in our qualitative analysis by System Organ Class (SOC), the highest level of the MedDRA medical terminology for each of the drugs studied. Results: The most frequent SOCs among the included drugs are investigations ( n  = 7 drugs); skin and subcutaneous tissue disorders ( n  = 5 drugs); and nervous system disorders, infections and infestations, gastrointestinal disorders, hepatobiliary disorders, and metabolism and nutrition disorders ( n  = 4 drugs). Other SOCs also emerged, such as general disorders and administration site conditions, renal and urinary disorders, vascular disorders and cardiac disorders ( n  = 3 drugs). Less frequent SOC were eye disorders, respiratory, thoracic and mediastinal disorders, musculoskeletal and connective tissue disorders, and immune system disorders ( n  = 2 drugs). Psychiatric disorders, and injury, poisoning and procedural complications were also reported ( n  = 1 drug). Conclusions: Some SOCs seem to be more frequent than others among the COVID‐19 drugs included, although neither of the studies included reported causality analysis. For that purpose, further clinical studies with robust methodologies, as randomised controlled trials, should be designed and performed.